ibn 'arabi dan teori al-llah al-ma'bud - Iskandar Arnel (An-Nida', 2013)
Global Theology ideas, Transcendental Unity of God, and Religious Pluralism. Among Muslims, the most so that the impression arises that eminent architect Wahdah al-existent concept is included in all the similarities about God that should be worshiped. This study found that Ibn ‘ Arabi accept and follow the teachings of the Apostles and the Book.